Liver histology of Wistar rats (Rattus norvegicus) following oral administration of 50% ethanol - Liah Kodariah; Rahmad Rezaldy; Suryanata Kesuma; Farhan Baehaki (Universitas Lampung, 2022)
Ethanol, also known as ethyl alcohol, pure alcohol, and alcohol, is a toxic, volatile, flammable, and colourless liquid. Alcohol is the most commonly consumed alcoholic beverage in everyday life. EtOH is a common abbreviation for ethanol, where